The desert as an expression of the dilemma of Brazilian politics in the face of the COVID-19 pandemic: an Arendtian analysis (Research, Society and Development, 2020)
In her text The Promise of Politics, Hannah Arendt presents us with the idea of the desert as a place of aridity and despair, in which totalitarian elements are presented preventing the formation of the common world and political action. With the current Brazilian government, which has a negative attitude towards the seriousness of the current sanitary, political and health crisis, it is clear that there is a policy of not taking any effective measures to combat the spread of the virus, adopting a authoritarian stance that prevents the implementation of more effective actions to contain the COVID-19 pandemic. The general objective of this article is to discuss how the Arendtian concepts of desert, oasis and promise can serve as an analysis of the Brazilian political situation during the pandemic of COVID-19 with regard to the performance of the federal government. Also using the narrative to better understand how authoritarian aspects of the Brazilian government helped to disseminate false information and maintain the desert situation, the method used will be inductive and bibliographic and documentary research. In this way, we can verify that even if the desert situation has installed itself, it does not mean the end of hope and the finding of ways out to combat the current pandemic crisis, because the promise means that the miracle and the new can guarantee solutions to the crisis. , initially through an oasis of narrative and in the construction of a space of common appearance to all Brazilians, as a result of political action.